RIMBA AS A PROTOTYPE DESIGN FOR AN EARTHQUAKE RESISTANT MODULAR HOUSE IN SWAMP AND PEAT LAND IN BARITO KUALA - Rizani, Muhammad Alfreno; Aina, Noor; Widyanti, Athica Yuhana; Nurpasha, Alya (Border: Jurnal Arsitektur, 2025)
South Kalimantan has 32.39% of its wetlands, consisting of swamps and peatlands, which are vulnerable to flooding and land fires. Furthermore, its hilly areas are also prone to flooding and landslides. In the past two years, five shallow earthquakes with intensities of MMI II–IV have increased the risk of disasters, although earthquakes were previously not a major threat. The frequent occurrence of building collapses reinforces the urgency of disaster mitigation and adaptation, particularly for residential housing. The primary research objective of this study is to develop a solution for safe, rapidly constructed, and disaster resilient housing. To this end, the RIMBA (Rumah Instan Modular Baja Ringan) prototype was conceived. This model employs a modular lightweight steel frame and GRC board walls, explicitly aiming to create an earthquake-resistant housing system. This design is adapted to soft soil conditions and earthquake potential, while prioritizing construction efficiency. The research was conducted through an digital experimental design approach and structural simulations with SAP2000. The results of the study show that the RIMBA design has structural performance equivalent to other earthquake-resistant buildings and is able to stand stably on an adaptive foundation, the development of the kacapuri foundation. With its easy-to-assemble modular material, RIMBA offers an efficient and feasible disaster-responsive housing solution, especially for communities living in swampy and peatland areas such as the Banjarmasin area.